Pengaruh Motivasi Karier, Sosial, Persepsi Biaya Pendidikan, dan Lama Pendidikan Terhadap Minat Mahasiswa Akuntansi untuk Mengikuti Pendidikan Profesi Akuntansi - I Made Prasetia Dwikamajaya; Ni Made Adi Erawati; Anak Agung Gde Putu Widanaputra; I Ketut I Ketut Sujana (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to find out how the interest of accounting students to take PPAk is influenced by career motivation, social, perceptions of educational costs, and length of education. 2018 FEB UNUD accounting students were used as the research population. as many as 72 respondents were selected using the accidental sampling method. Multiple linear regression analysis was used for data analysis. The results of the various tests used state that the interest of accounting students is influenced by career, social, perceived cost of education, and length of education to attend PPAk. The results of this research can serve as information or reference for other similar researchers and can also assist related institutions in providing information or references to increase student interest in participating in the PPAk program. Keywords : Career motivation, social, perceived tuition fees, length of education, interest, PPAk.